Zingiber sabuanum (Zingiberaceae): a new species from Kerala, India - Prabhukumar, Konickal Mambetta; Joe, Alfred; Balachandran, Indira (Phytotaxa, 2016)
Zingiber Miller (1754: 525; Zingiberaceae) it is distinct from other genera of the family in having a single anther with a beak or horn-like appendage, wrapping around the upper part of style (Sabu et al. 2013). It is considered the largest genus in subfamily Zingiberoideae with 100–160 species globally and is distributed in tropical to warm-temperate Asia with the highest diversity in the monsoonal parts of Asia (Govaerts et al. 2016, Leong-Skornickova et al. 2015). In India, the genus is represented by 29 species (Kumar et al. 2015), of which eight are recorded from South India (Sabu 2006).